2012
DOI: 10.1021/ie3008133
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation and Flame Retardance of Biobased Polylactide Composites Based on Aluminum Hypophosphite

Abstract: A series of flame retardant polylactide composites (FR-PLA) based on aluminum hypophosphite (AHP) were facilely prepared by melt blending method. The thermal behavior, flammability, and mechanical properties of FR-PLA composites were investigated by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), the UL-94 vertical burning test, limiting oxygen index (LOI), cone calorimeter testing, microscale combustion calorimetry, mechanical testing, and dynamic mechanical analysis (DMA). TGA resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 167 publications
(137 citation statements)
references
References 31 publications
8
128
0
1
Order By: Relevance
“…The good compactness and continuity of char layer are known to be efficient and beneficial with respect to thermal and mass loss insulation. 35 After a cone calorimeter test, hoary crystals with gloss were observed on the surface of exterior char for MoS 2 /GNS/EP composites. The exterior and interior chars of MoS 2 /GNS/EP composites were more surveyed by XRD analysis.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…The good compactness and continuity of char layer are known to be efficient and beneficial with respect to thermal and mass loss insulation. 35 After a cone calorimeter test, hoary crystals with gloss were observed on the surface of exterior char for MoS 2 /GNS/EP composites. The exterior and interior chars of MoS 2 /GNS/EP composites were more surveyed by XRD analysis.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…It has no obvious cold crystallization temperature, which is consistent with the relevant research. 19 The incorporation of LaHP and CeHP does not significantly change the T g value of the composites, but the T m value is slightly increased. The T c is also found to be consistent with the above literature.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Braun and Schartel found that aluminum hypophosphite exhibited good flame retardance for glass fiber reinforced PA-6,6. 18 Furthermore, Tang et al 19 introduced aluminum hypophosphite into polylactide and found that 20 wt % AHP loading resulted in a V0 rating in UL-94 testing.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, AHP as a novel class of phosphorous-based flame retardants, which is expected as a promising candidate for replacing halogenbased flame retardants, also it has been applied in the treatment of organic materials such as glass-filled polyamide 6 [3], polybutylene terephthalate (PBT) [4,5], poly(ethylene terephthalate) [6], and polylactide [7]. These publications have described the flame retardancy and speculated the thermal degradation mechanism of the metal hypophosphites.…”
Section: Introductionmentioning
confidence: 99%